2018
DOI: 10.1111/jfs.12602
|View full text |Cite
|
Sign up to set email alerts
|

An approach to improve the safety and quality of ready‐to‐eat blueberries

Abstract: Bioactive edible coatings were developed and applied to blueberries as a natural treatment. E. coli O157:H7, L. innocua, S. aureus, and P. aeruginosa were subjected to four bioactive compounds and to three film‐forming solutions (FFS). Vanillin and geraniol at low concentrations (1.2–1.8 mg/mL and 0.4–1 μL/mL) demonstrated significant inhibitory effects on all pathogens counts. Chitosan (Ch) showed a high antimicrobial activity (final counts below 2 log CFU/mL). The effectiveness of Ch plus vanillin (Ch‐Va) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The disc-diffusion study showed that pullulan coating incorporated with pecan shell extracts were effective against S. aureus and S. enterica ( Table 1 ), but during the in vivo study on blueberry no significant effect of extract was observed. Several studies have observed this phenomenon of decreasing efficacy of bioactive compounds from in vitro to in vivo owing to slow and selective movement of compounds from coating to the fruit surface thus reducing its effectiveness during storage [ 34 , 35 ]. Studies have shown that the antimicrobial efficacy of pecan shell extract are also pathogen and strain specific [ 7 , 11 ] thus, different strains of bacteria used in the antimicrobial coating study which was not used during the disc-diffusion antimicrobial screening study may have been the reason for organism's resistance towards the shell extracts.…”
Section: Resultsmentioning
confidence: 99%
“…The disc-diffusion study showed that pullulan coating incorporated with pecan shell extracts were effective against S. aureus and S. enterica ( Table 1 ), but during the in vivo study on blueberry no significant effect of extract was observed. Several studies have observed this phenomenon of decreasing efficacy of bioactive compounds from in vitro to in vivo owing to slow and selective movement of compounds from coating to the fruit surface thus reducing its effectiveness during storage [ 34 , 35 ]. Studies have shown that the antimicrobial efficacy of pecan shell extract are also pathogen and strain specific [ 7 , 11 ] thus, different strains of bacteria used in the antimicrobial coating study which was not used during the disc-diffusion antimicrobial screening study may have been the reason for organism's resistance towards the shell extracts.…”
Section: Resultsmentioning
confidence: 99%
“…The analyses of microbial contamination such as aerobic bacteria, molds, and yeasts counts were evaluated at an interval of three days and carried out up to nine days during storage according to the methodology described by Bambace et al [ 44 ]. Aerobic bacteria, molds, and yeasts were performed using a rose bengal medium (GB4789.15-2016) and (GB4789.2-2016), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In order to obtain biopreservatives-enriched chitosan solutions, a portion of 1.5% Ch solution was added with 1.8 mg/ml of vanillin (Sigma-Aldrich, Argentina), obtaining Ch-V treatment (1.5% chitosan coating enriched with 1.8 mg/ml vanillin), meanwhile another portion of the base coating was enriched with 1 μl/ml of geraniol (Sigma-Aldrich, Argentina), obtaining Ch-G solution (1.5% chitosan coating enriched with 1 μl/ml geraniol). The concentrations used for the bioactives enrichment correspond to the minimum inhibitory concentration of each compound previously obtained by Bambace, Gerard, and Moreira (2019).…”
Section: Chitosan Coating Solutionsmentioning
confidence: 99%